Compulsion - Norman, Hilary (London : Piatkus, 2005)
Frankie Barnes had a tormented life until she found the perfect career to suit her obsession with hygiene. As a cleaner, she can scrub away to her heart's content at her clients' homes, be paid and even valued for her pains. But Frankie suffers from other compulsions too and the greatest of them all is the compulsion to have.
National College of Business and Arts
Keywords: Compulsive behavior -- Fiction; Thrillers (Fiction)